Aging Meaningfully: The Ethics of Existential Suffering for Older Adults in Healthcare - Tsai, Gabrielle (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2024)
Existential suffering (ES) can be particularly prevalent among older adults, and with Canada’s growing aging population, addressing ES in senior care will be a pressing concern in coming years. ES is a side effect of aging that involves losing meaning, self-identity, autonomy, and hope. This paper focuses on one cause of ES among older adults, namely, the loss of meaning (LoM). Meaning becomes increasingly necessary for well-being at later stages in life, due to the positive effects it confers on mood, health, and longevity. I argue that when ES arises in healthcare settings, healthcare providers (HCPs) have a duty to 1) understand ES and LoM and 2) respond to older adults who experience ES because of LoM. HCPs may not be able to alleviate ES or LoM, but they are obliged to make a reasonable attempt. To justify this, I draw upon three fundamental values in healthcare: trust, compassion, and beneficence. By reflecting on each of these values, it becomes clear that ES and LoM deserve attention from HCPs. In addition to making this argument, I recognize that ES is not only limited to old age nor solely incumbent on HCPs to address. Broader social factors and public health initiatives can help people at all life stages to preserve meaning. In raising awareness in HCPs about ES due to LoM, this paper also provides a non-exhaustive list of three psychotherapies that deserve exploration and/or implementation for patients suffering from ES due to LoM, namely: Palliative Care Psychotherapy, Meaning-Centred Group Psychotherapy, and Dignity Therapy.